PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DAN WEIGHTED PRODUCT (WP) DALAM SISTEM PENUNJANG PEMILIHAN LAPTOP TERFAVORIT MENGGUNAKAN GUI MATLAB - Abdiel Pandapotan Manullang; Alan Prahutama; Rukun Santoso (Jurnal Gaussian, 2018)
Laptops have become an important requirement for most students is to support educational activities and business activities. The number of brands of laptops or types of laptops that exist makes consumers especially students have their own preferences in choosing a laptop. The method can be used to select the favorite laptop are SAW (Simple Additive weighting) and WP (Weighted Product). Both of these methods are the methods used to solve the problem of MADM (Multi Attribute Decision Making). There are 30 types of laptops that will be used in the selection of the favorite laptops.For the selection criteria for the type of laptop that is priced, RAM (Random Access Memory), HDD (hard drive), a processor, a VGA (Video Graphics Array), weight, color, screen size, service centers, warranty, availability of spare parts, battery capacity, equipped with OS and application software. Selection of the favorite type of laptop is done with the help of MATLAB (Graphical User Interface) GUI (Matrix Laboratory) as a computing tool. SAW method and WP, in this research showed the same results that the most favored type of laptop laptop mode DEL INSPIRON 15Z-5523 with a value preference for SAW method amounted to 0.9518 while the WP method amounted to 0.9511.Keywords: SAW, WP, Laptop, favorite, GUI